Compositional and Surface Morphological Analysis on Indium Tin Oxide Thin Films Prepared by Radio Frequency Sputtering - Malathy1, V.; Balasubramanian1, T.; Jayach, M. (Asian Journal of Chemistry, 2013)
In the present work, we report the results of compositional and surface morphological analysis on indium tin oxide thin films prepared by RF magnetron sputtering of a ceramic oxide target with quartz substrate under Ar gas atmosphere. Radio frequency power and substrate temperature were held at 250 W and 150 ºC respectively. Indium tin oxide films were characterized by EDX, XPS and TEM analysis. TEM images evidence the formation of crystalline indium tin oxide films with nano grained structure. XPS study shows the substitution of In3+ sites with Sn4+ and EDX result reveals the uniform distribution of In and Sn on the surface supported by the smoother surface with nano grains. These results reveal that a combination of high RF power (250 W) and moderate substrate temperature (150 ºC) is capable of producing thermally stable and device quality indium tin oxide films.